Environmental awareness and pro-environmental behavior within China's road freight transportation industry: Moderating role of perceived policy effectiveness. (10th April 2020) - Fu, Liping; Sun, Zhaohui; Zha, Lajia; Liu, Feng; He, Lanping; Sun, Xuesong; Jing, Xiaoli
Abstract: Road freight transportation (RFT) has received significant attention from the government, industry, and academia because of its high energy consumption and carbon emissions. To reduce the negative effects of the accelerating use of RFT, China has recently been committed to promote green RFT. Efforts made in this direction have mainly focused on supply-side policy and technical measures, while neglecting the importance of demand-side psychological and behavioral strategies. Recent research suggests that drivers play a fundamental role in generating environmental impacts during transport. Thus, the success of green RFT should also be based on a thorough understanding of the drivers' environmental awareness and pro-environmental behavior. In this study, we investigate the current levels of environmental awareness and pro-environmental behavior among China's RFT drivers, and explore the role of environmental awareness as defined by four main components—environmental concern, environmental attitude, environmental knowledge, and behavioral intention—in motivating pro-environmental RFT behavior. We also test the moderating effect of perceived policy effectiveness on the awareness–behavior relationship. Hypotheses are examined using a sample of 243 truck drivers with structural equation modeling and hierarchical regression analysis. The results indicate the existence of an environmental awareness–behavior gap. We determine that the awareness score (3.2) is higher than the behavior score (3.1) because barriers to pro-environmental behavior are stronger than motivators. We also find that environmental concern, attitude, and knowledge indirectly affect pro-environmental behavior via behavioral intention. Moreover, a high level of perceived policy effectiveness facilitates the transformation of awareness into behavior, bridging the awareness–behavior gap. Our study confirms the importance of environmental awareness and effective incentive policies in encouraging pro-environmental RFT behavior. The conclusions will aid researchers' understanding of drivers' environmental awareness and pro-environmental behavior in China's RFT, and compel transport policy makers and managers to implement more effective measures that promote environmentally sustainable RFT. Highlights: This study investigated environmental awareness and pro-environmental behavior within China's RFT context. Drivers' awareness score is higher than their behavior score, indicating a gap. Environmental concern, attitudes, and knowledge indirectly affect behavior via behavioral intention. Perceived policy effectiveness helps transform awareness into behavior, thereby bridging the awareness–behavior gap. The findings are valuable for transport policy makers and managers who are seeking to promote sustainable RFT.